Analisis Modal Kredit Usaha Rakyat dalam Meningkatkan Perkembangan UMKM dI Kota Tengah: Studi Kasus UMKM Dwi Laundry dan Toko Olfan - Dinda Resti Umar; Ronald Soemitro Badu; Yustina Hiola (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the ideal working capital for MSMEs in the Central City District. The research used a quantitative approach with descriptive methods. The sample in this study was two MSMEs where data collection used observation, interviews and documentation. The data analysis technique uses debt ratio analysis, maximum loan analysis and calculation analysis of business capital sources from loans. The results showed that People’s Business Credit capital has a positive impact on improving the income and operations of MSMEs. Dwi Laundry and Toko Olfan recorded increased revenues thanks to the use of People's Business Credit capital, which allowed for increased operational capacity and improved financial performance from year to year. However, the research also found that MSME owners tend to use business income for personal purposes, which leads to confusion between personal and business finances and hinders strategic decision-making.